Persepsi Karyawan Mengenai Workplace Well-Being pada Karyawan PT. Trans Pacific Atlantic Lines - Marlev Christon Ririmasse; Sukmarani Sukmarani (Universitas Muhammadiyah Jember, 2022)
Workplace well-being is one of the important factors for an organization or company. This study aims to explore the perceptions of employees of PT. TPAL regarding their workplace well-being. This research was conducted to provide information to companies regarding their employee wee-being at work. Workplace Well-Being is influenced by two dimensions, namely the intrinsic, extrinsic, and also core affect aspects. The question that needs to be answered in this research is whether there is a high level of well-being at the workplace for the employees of PT. TPAL. Participants in this study were all employees of PT. TPAL totaled 30 people. The results indicated that the intrinsic dimensions that affect the workplace well-being are in the high category, while the extrinsic dimensions are in the medium category.